Authoritarian diasporas in Indonesia and the Philippines: comparative perspectives on elite survival and defection. Issue 3 (3rd April 2021) - Buehler, Michael; Nataatmadja, Ronnie
ABSTRACT: The article compares the political trajectories of authoritarian diasporas in Indonesia and the Philippines, namely the subset of former regime officials that disperse across the electoral space after a regime transition. The main finding is that after the Suharto and Marcos dictatorships collapsed in 1998 and 1986 respectively, Indonesia's authoritarian successor party (ASP) fared better than the ASP in the Philippines. However, the authoritarian diaspora did better in the Philippines than in Indonesia. Engaging with existing scholarship on authoritarian successor parties and authoritarian diasporas, the article argues that the two variables shaping defection calculi are the prevailing levels of party institutionalization of both the authoritarian successor party and alternative parties as well as the type of reversionary clientelistic network available to elites in post-transition politics.